Minimization of Pollution Concentration on a Given Time Interval for the Waste Water Cleaning Plant - E. V. Grigorieva; E. N. Khailov (Journal of Control Science and Engineering)
A model of a waste water treatment plant is investigated. The model is described by a nonlinear system of two differential equations with one bounded control. An optimal control problem of minimizing concentration of the polluted water on the given time interval is stated and solved analytically with the use of the Pontryagin Maximum Principle and Green's Theorem. Computer simulations of a model of an industrial waste water treatment plant show the advantage of using our optimal strategy. Possible applications are discussed.